2004
DOI: 10.1074/jbc.m406932200
|View full text |Cite
|
Sign up to set email alerts
|

Only a Portion of the Small Seatbelt Loop in Human Choriogonadotropin Appears Capable of Contacting the Lutropin Receptor

Abstract: Twenty residues of the human choriogonadotropin (hCG) ␤-subunit that are wrapped around ␣-subunit loop 2 like a "seatbelt" stabilize the heterodimer and enable the hormone to distinguish lutropin (LHR), follitropin, and thyrotropin receptors. The N-terminal portion of the seatbelt contains a small disulfide-stabilized loop needed for heterodimer assembly and is thought to mediate hCG-LHR interactions. To test the latter notion, we compared the LHR binding and signal transduction activities of hCG analogs in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…the "determinant loop") and the ␣-subunit COOH terminus, this requires that the ligand be oriented perpendicular to the LRD (5), an orientation that does not lend itself well to models of signal transduction. Furthermore, it does not explain the findings that the ␣-subunit COOH terminus can be cross-linked to most residues of the hCG small seatbelt loop by a disulfide without altering hormone activity (76).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…the "determinant loop") and the ␣-subunit COOH terminus, this requires that the ligand be oriented perpendicular to the LRD (5), an orientation that does not lend itself well to models of signal transduction. Furthermore, it does not explain the findings that the ␣-subunit COOH terminus can be cross-linked to most residues of the hCG small seatbelt loop by a disulfide without altering hormone activity (76).…”
Section: Discussionmentioning
confidence: 92%
“…Antibody binding data also revealed that the conformation of the tip of ␤-subunit 3 is altered on receptor binding (53). In revising our initial model, we made use of unpublished data (75,76) obtained with a technique developed to probe distances of specific residues in all three hormones and their receptors (data described in Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least two peptide regions located between cysteine residues b38 -57 and b93 -100 (Prasad et al, 2007) named receptor-determined loops, within the hCGb which confer receptor specificity. The surface able to activate the hCG receptor would include the majority of the hCGa and the Asp-99 residue contained in loops b93 -100 (Bernard et al, 2004). The CTP hCGb, not important for receptor binding or in vitro signal transduction, is critical for in vivo biological response (Chen and Puett, 1991).…”
Section: Biological Activity Of Hcgmentioning
confidence: 99%